Comparison of Indonesian President Jokowi's Political Victory Strategy and Malaysia's Anwar Ibrahim - Agus Machfud Fauzi,; Refti Handini Listiyani,; Muhammad Arif Affandi,; Silkania Swarizona,; Anam Miftahul Huda,; Maya Mustika Sari, (Technium Social Sciences Journal, 2023)
Joko Widodo Indonesia's Winning Strategy in the 2019 Presidential Election and Malaysia's Anwar Ibrahim in the 2022 Election are interesting strategies for scientific knowledge. The purpose of this study is to reveal how the winning strategy was carried out by Pak Jokowi who was attacked by Prabowo's political opponents, and Anwar Ibrahim who took 24 years to win. This study uses a qualitative method using the comparative theory of victory for the winning strategy between the two political actors. The results of the study show that Anwar Ibrahim and Jokowi both won the contest for the election of the prime minister in Malaysia and the president in Indonesia. The difference is that Anwar Ibrahim used the strategy of fighting the persecuted people until he got the power to win, while Jokowi won with the strategy of showing criticism of the first period's rulers, while in the second period, the winning strategy was by gathering all political forces with the hegemony of the incumbent.